PRINSIP-PRINSIP PERKEMBANGAN PRINSIP-PRINSIP PERKEMBANGAN: PRINSIP-PRINSIP PERKEMBANGAN - Imam Mashudi; Alun Matiti (LPPM UNiversitas Bina Mandiri Gorontalo, 2021)
Development is one of the important stages in the process of everyone's life. Every human being continuously develops, the development that occurs in each person has factors that influence both internal and external factors, both developments are influenced by learning or experience. Development occurs gradually from humans from birth to old age. This research was conducted to find out the principles of development that occur in humans from birth to elderly humans. From this research it can be known the principles of human development in stages. Early Development More critical than Subsequent development when children aged 0-5 years is a critical time for further development. Early life development is the basis for the formation of the basic principles of one’s personality. Patterns of development, in addition to following certain predictable patterns, there are also certain patterns of characteristic development. Development moves from general to more specific responses. Development is taking place continuously